The 2021 WHO Classification of Tumors of the Central Nervous System: a summary. Issue 8 (29th June 2021) - Louis, David N; Perry, Arie; Wesseling, Pieter; Brat, Daniel J; Cree, Ian A; Figarella-Branger, Dominique; Hawkins, Cynthia; Ng, H K; Pfister, Stefan M; Reifenberger, Guido; Soffietti, Riccardo; von Deimling, Andreas; et al.
Abstract: The fifth edition of the WHO Classification of Tumors of the Central Nervous System (CNS), published in 2021, is the sixth version of the international standard for the classification of brain and spinal cord tumors. Building on the 2016 updated fourth edition and the work of the Consortium to Inform Molecular and Practical Approaches to CNS Tumor Taxonomy, the 2021 fifth edition introduces major changes that advance the role of molecular diagnostics in CNS tumor classification. At the same time, it remains wedded to other established approaches to tumor diagnosis such as histology and immunohistochemistry. In doing so, the fifth edition establishes some different approaches to both CNS tumor nomenclature and grading and it emphasizes the importance of integrated diagnoses and layered reports. New tumor types and subtypes are introduced, some based on novel diagnostic technologies such as DNA methylome profiling. The present review summarizes the major general changes in the 2021 fifth edition classification and the specific changes in each taxonomic category. It is hoped that this summary provides an overview to facilitate more in-depth exploration of the entire fifth edition of the WHO Classification of Tumors of the Central Nervous System.